Implementation of Business Intelligence in Supporting Decision-Making for Population and Family Planning Programs: A Qualitative Study at the Population Control and Family Planning Office of Sorong City - Ulil Albab Al Jawad (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the implementation of Business Intelligence (BI) in supporting decision-making for population and family planning programs at the Population Control and Family Planning Office of Sorong City. Using an empirical qualitative approach, the research explores how BI systems are utilized, how analytical outputs inform managerial decisions, and which organizational factors shape their effectiveness. Data were collected through in-depth interviews, observations, and document analysis involving policymakers, program managers, data analysts, and technical staff. The findings reveal that BI facilitates data integration across program units, enhances the timeliness and relevance of information, and supports evidence-based planning, monitoring, and evaluation. Dashboards and analytical reports enable decision-makers to identify demographic trends, assess program performance, and adjust interventions responsively. However, the effectiveness of BI is contingent upon data governance, human resource capacity, and institutional commitment to data-driven practices. The study highlights BI as a technological and managerial innovation that strengthens decision quality and institutional resilience in local public sector governance, particularly in population and family planning services..